Anatomical Remodeling of Buccal Bone Plate in 35 Premaxillary Post-Extraction Immediately Restored Single TPS Implants: 10-Year Radiographic Investigation. Issue 2 (April 2016) - Quaranta, Alessandro; Perrotti, Vittoria; Putignano, Angelo; Malchiodi, Luciano; Vozza, Iole; Calvo Guirado, José Luis
Abstract : Purpose: The anatomical remodeling technique (ART) was proposed to place postextraction implants with the aid of specific osteotomes. This study is a clinical and radiographic evaluation with 10-year follow-up of anterior postextraction single implants placed with the ART and immediately restored. Materials and Methods: Thirty-five patients, with a hopeless tooth in the anterior maxilla, were included in the study and 35 implants were inserted according to the ART. Clinical and radiographic evaluations were performed at baseline (T0), after 6 (T1) and 14 months (T2), 4 years after surgery (T3) and every other year up to the 10-year follow-up (T4, T5, and T6). Implant success, survival, and failure rates were evaluated according to the International Congress of Oral Implantologists Pisa Consensus Conference criteria. Results: Twenty-nine patients and 29 implants were available for the 10-year data analysis. After 10 years, the accumulated mean marginal bone loss was 2.69 ± 0.42 mm. The cumulative survival rate of the implants was 100%. Conclusions: Immediately loaded postextractive implants, placed according to the ART, have been proved to be a predictable method to rehabilitate single tooth in the anterior maxilla.